Carcinoma of sweat gland with ganiglionic metastasis - Perrone, Luis; Bounous, Mario; Lerena, Ana; Pamparato, Mario; Bosch, Gonzalo; Beriao, Juan Carlos (Cirugía del Uruguay, 1977)
In the case of a woman suffering from carcinoma of axilary sweat gland, precisa diagnosis was established; therapy consisted solely of surgery and evolution has been acceptable. A review of this disease is included in the paper.